EFFORTS TO PREVENT THE SPREAD OF COVID-19 IN RECITATION/TPA PARTICIPANTS AT ISLAMIC CENTER MOSQUE, LHOKSEUMAWE CITY - Teuku Ilhami Surya Akbar; Sarah Rahmayani Siregar (Global Science Society, 2022)
Since Indonesia was declared on alert for Covid-19 in March 2020, the number of patients has shown an increasingly worrying spike, both national and worldwide data. The government is currently imposing a "new normal" to move the wheels of the economy, such as mosques or places of worship also starting to open along with activities in them such as recitation at mosques. The easing or implementation of this new order of life will have an impact if a good strategy is not implemented to prevent the spread of Covid-19, especially in mosques that have begun to open and recitations held in them. The output target of the community service activities from the aspect of the health service program is the availability of the Covid-19 health protocol at the place of recitation, while the target aspect of health service supporting facilities is the availability of Covid-19 prevention facilities for the recitation participants.